Blockchain Technology in Healthcare Data - Chowdhury, Baishakhi (My University, 2024)
Healthcare data is characterized by its sensitivity and criticality, comprising a wide range of information critical to patient care and medical research. Blockchain technology has revolutionized healthcare data management by providing enhanced security, transparency, and accuracy. This thesis explores blockchain's disruptive potential in healthcare, emphasising on its applications in various sectors of the healthcare industry. Blockchain has numerous advantages in healthcare, including its ability to improve data integrity, streamline processes, and improve patient outcomes. To ensure efficiency and security, blockchain technology can revolutionize healthcare applications such as Electronic Health Records (EHR), clinical trials, pharmaceutical sector operations, and claim and billing management. Several blockchain solutions have emerged to address the unique challenges of healthcare data management, including MedRec, BitHealth, MedBlock, MedChain, and MedShare. These platforms present novel techniques for securely storing and sharing healthcare data, opening the path for a more linked and patient-centric healthcare environment. Despite its potential benefits, integrating blockchain into healthcare is not without challenges. Technical complexity, standards issues, interoperability concerns, and regulatory compliance are significant obstacles to broader use. Furthermore, the thesis provides case studies of countries that have effectively used blockchain in healthcare, highlighting best practices and lessons learned from these initiatives. This research study contributes to the existing discussion about blockchain's disruptive impact on the healthcare industry by examining real-world uses of the technology in healthcare settings.
Keywords: Healthcare data, blockchain, distributed ledger technology, applications of blockchain, security